Subjective and objective results 1 year after robotic sacrocolpopexy using a lightweight Y-mesh - Culligan, Patrick J. (Int Urogynecol J, 2013)
INTRODUCTION AND HYPOTHESIS: The objective of this study was to assess outcomes following robotic sacrocolpopexy using a lightweight polypropylene Y-mesh. METHODS: During our study period, all patients who underwent robotic sacrocolpopexy were enrolled in this single-arm prospective trial. Endpoints included Pelvic Organ Prolapse Quantification (POP-Q) values; Pelvic Floor Distress Inventory, short form 20 (PFDI-20); Pelvic Floor Impact Questionnaire, short form 7 (PFIQ-7); Surgical Satisfaction scores; and the Sandvik Incontinence Severity Index. All surgeries were performed with a pre-configured monofilament type 1 polypropylene Y-mesh (Alyte©, C.R. Bard, Covington, GA, USA). Cure rates at 12 months were calculated using two separate definitions: (1) “clinical cure”: no POP-Q points > 0, point C ≤ −5, no prolapse symptoms on the PFDI-20, and no reoperations for prolapse and (2) “objective anatomic cure”: POP-Q stage 0 or 1, point C of ≤ −5, and no reoperations for prolapse. RESULTS: A total of 150 patients underwent robotic sacrocolpopexy and 143 (95 %) were available for 12-month follow-up. Mean age was 58.6 ± 9.8 and mean body mass index was 26.3 ± 4.5. Mean operative time and blood loss were 148 ± 27.6 min (range 75–250 min) and 51.2 ± 32, respectively. There were no mesh erosions or exposures, and mesh edges were not palpable in any patient. At 12 months the clinical cure rate was 95 %, and the objective anatomic cure rate was 84 %. The PFDI-20 mean score improved from 98 at baseline to 17 at 12 months (p < 0.0001); PFIQ-7 scores improved from 59 to 6.5 (p < 0.0001). CONCLUSIONS: Robotic sacrocolpopexy using this lightweight polypropylene Y-mesh offers excellent subjective and objective results at 1 year.